A broadly narrow map of intellectual traditions - Canham, Hugo (PINS-Psychology in Society, 2024)
Vale, Peter, Hamilton, Lawrence & Prinsloo, Estelle H (eds) (2014) Intellectual traditions in South Africa: Ideas, individuals and institutions. Pietermaritzburg: University of KwaZulu-Natal Press. ISBN 978-1-86914-258-2 pbk. Pages xii + 364.